Slacking On: Lean Practices in Applied Education (Journal of Applied Learning and Teaching, 2020)
Applied educators experience both increased rewards and increased burden as a result of the inherent impact, complexities, and risks of executing applied and community-based learning projects.  A “lean”, resource-mindful approach to career management is recommended in order to ameliorate risk, optimize student and community outcomes, and sustain effective engagement over time. Keywords:  Applied learning, community-based learning, lean practices, risk management.